Women of Color Student Survivors' Perceptions of Campus Sexual Assault Prevention Programming. (December 2022) - Karunaratne, Nadeeka; Harris, Jessica C.
This article presents a qualitative study of 44 Women of Color undergraduate student survivors' perceptions of campus sexual assault prevention programming using the framework of standpoint theory. Participants held perceptions concerning online training prior to college, the in-person presentations they attended during new student orientation, and the lack of information relayed through prevention programs about sexual assault perpetration. Findings highlight the need for continued research investigating the standpoints of Women of Color students to better inform implementation of prevention efforts.